The State of Research on Islamic Spain (American Journal of Islam and Society, 1992)
The era of Muslim rule in Spain (711-1491 CE) witnessed great contributionsin many areas of knowledge and learning. Rapid strides weremade in such diverse fields as art and architecture, agriculture and handicrafts,linguistics and literature, humanities and Social studies, music andpoetry, and the physical and mechanical sciences. In fact, Islamic Spain,known to the Muslim world as al Andalus, served as a bridge for thetransfer of the knowledge and wisdom of Classical Greece to Europe, aprocess that eventually led to the European Renaissance.The achievements of al Andalus will not be discussed in this paper.Rather, a survey of current research activities focusing on al Andaluswill be presented. The areas covered are Europe, North America, NorthAfrica, and parts of Asia. Latin American activities have not been surveyeddue to the nonavailability of sources.EuropeEurope has been the center of research on al Andalus. Various periodicalshave served as major sources of information: Al-Andalus (Madrid1933), Hesperis (Paris 1921-59), Hesperis-Tamuda (Rabat 1960), Miscellanceade Estudios Arabes y Hebraicos (Granda 1952), Revista de InstitutoEgypcio de Studios Islamicos (Madrid 1953), Revue de la OccidentMusulman et la Mediterranee (Aix-en-Provence 1966), Boletin de laAssociation Espaniola de Orientalistas (Madrid 1965), and Cuadernos dela Alhambra (Granada 1965).Certain important books have also appeared, such as Peres: la PoisieAndalousie, which includes a history of that period. Introductions to editionsof texts and translations relate important infonnation about al Andalusunder the al Murabitun and the al Mu’ahhidun dynasties. Hourani(1961) has written an excellent book: Averroes: On the Harmony of Religionand Philosophy. Memorial volumes in honor of E. Levi-Provencal,G. and W. Marcais, Menendes Pidal, Millas Vallicrosa y Parya, A. H. andR. Basset, H. A. R. Gibb and H. Wehr also contain much valuable data.Mention must be made of translations by institutes devoted to thestudy of al Andalus: Dar al Thaqafah (Beirut) has published valuablebooks, as have several Spanish and North African organizations (i.e.,Conjeyo Superior de Investigaciones Cientificas Madrid], Instituto deStudios Islambs [Madrid], Institute des Haut-Etudes Marocaines Paris ...